KONSEP BERKAH (BARAKAH) DALAM PERSPEKTIF QUR’AN DAN HADITS SERTA IMPLEMENTASINYA DALAM PENDIDIKAN - Burhanuddin, - (Al Tadib : Jurnal Ilmu Pendidikan, 2017)
This article discusses the concept of blessings in perspective implemetasinya Qur'an Hadith as well as in education. The concept of blessing (baraka) in the perspective of the Qur'an is as the description that has been described in the verses which explain about the blessing (baraka) that relates to a person who is loved by Allah SWT that is in Q.S. Hud: 48, Q.S.An-Naml: 8 Q.S.Ash-Saffat: 113, and Q.S.Maryam: 31. And the blessing that relates to the place: Q.S.ali-Imran: 96, Q.S.al-Isra ': 1, and Q.S. al-Qasas: 30. blessing that relates to something or objects: Q.S.al-An'am: 155, Q.S. An-Nur: 35, and Q.S. Qaf: 9, and the blessing that relates to time: Q.S. ad-Dukhon: 3. blessing that relates to actions in the previous race Q.S. Al-Baqarah: 248, and QSYusuf: Medium concept of blessing (baraka) In a hadith perspective as the description that has been described in hadiths about taking the blessing of the Companions of the Holy Prophet former ablution water and hadith about picking up blessing the companions of the Prophet heritage, And Implementation of the concept of blessing (baraka) in education is by planting attitude expect a blessing to Allah both on students and teachers, with the aim to obtain useful knowledge and blessings. Therefore adab ethics for obtaining useful knowledge and blessings in the process of teaching and learning activities that taught the Quran and hadith they all should run. Keywords: Concepts Barakah, the perspective of Quran and Hadith, Education